Ecosystem consequences of herbicides: the role of microbiome - Ruuskanen Suvi; Fuchs Benjamin; Nissinen Riitta; Puigbò Pedro; Rainio Miia; Saikkonen Kari; Helander Marjo (ELSEVIER SCIENCE LONDON, 2025)
Non-target organisms are globally exposed to herbicides. While many herbicides for example, glyphosate - were initially considered safe, increasing evidence demonstrates that they have profound effects on ecosystem functions via altered microbial communities. We provide a comprehensive framework on how herbicide residues may modulate ecosystem-level outcomes via alteration of microbiomes. The changes in soil microbiome are likely to influence key nutrient cycling and plant-soil processes. Herbicide-altered microbiome affects plant and animal performance and can influence trophic interactions such as herbivory and pollination. These changes are expected to lead to ecosystem and even evolutionary consequences for both microbes and hosts. Tackling the threats caused by agro-chemicals to ecosystem functions and services requires tools and solutions based on a comprehensive understanding of microbe-mediated risks.